Monetization of Economy and Inflation: Two Antagonisms in Home Finance System - A. I. Bolvachev; V. M. Savradym (Вестник Российского экономического университета имени Г. В. Плеханова)
Economy growth in the country is accompanied by rising volumes of its monetization. The more economy is monetized, the lower impact of inflation as a destabilizing factor of the system becomes. The article studies the essence of this correlation within the frames of Russian economy. The research consists of 3 sections: the 1st one describes methodology of estimating economy monetization level. On the basis of the analysis problematic aspects in validity of using estimation parameters were identified. For instance, inadequacy of GDP factor as an indicator of economy development was highlighted. At the same time by successive analysis of monetary aggregate used in calculation of economy monetization factor drawbacks of aggregates M3 and M2 were found and the use of weighted average of M2 was grounded. Comparative analysis of estimation results through different methodology depending on monetary aggregate showed serious discrepancy and therefore, the real degree of under-monetization of country economy. The 2nd section of the research studies indicator of the monetary system stability, i. e. inflation rate. The article provides analysis of correlation between inflation rate and other parameters of the finance system (in the context of its monetary and credit segment) – money supply and key interest rate. Results show the change in trajectory of the assumed correlation since 2013, which allows us to draw a conclusion about prevailing impact of non-monetary factors on inflation rate. The 3rd section of the research, focusing on investigation of correlation analysis results deals with correlation between economy monetization level and inflation rate. The calculation section of the research uses a lot of visual material, which improves comprehension of the research findings. The analytical period of the research makes 27 years.